Zarządzanie ryzykiem środowiskowym jako podstawa decyzji menedżerskiej - Panasiewicz, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
All kinds of people activity can cause a risk. The risk is an impediment not only for people health and their life, but also for the activity which is lead by them and for the nature which surrounds them. The consequence of that situation is the quality of environment which still becomes worse and worse. The increase in the pollution including the different components of the nature requires the interest of ecological subject which therefore becomes more and more important. The aim of the activity taken in all the world is to preserve a good quality and people friendly nature of environment. One of the elements of that activity is the development of the environmental risk management process. It includes two stages: 1) Stage of risk analysis - this is an analytic part of all processes; 2) Stage of risk inspection (management, manipulation - procedure) - this part of the process lets take decission on "how to reduce or eliminate existing impediment and how to finanse the cost of that undertaking". (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 229-238